2007
DOI: 10.1007/bf02977327
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of beryllium induced hepatorenal dysfunction and oxidative stress in rodents by combined effect of gallic acid and piperine

Abstract: We determined a minimum effective dose of gallic acid (3,4,5-trihydroxy benzoic acid; 50 mg/ kg, i.p.) and piperine (10 mg/kg, p.o.) through their therapeutic potential and further evaluated them individually and in combination against beryllium-induced biochemical alterations and oxidative stress consequences in female albino rats. The administration of beryllium altered blood biochemical variables by significantly depleting hemoglobin, albumin and urea, whereas it enhanced bilirubin and creatinine. The relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…They observed that individual administration of gallic acid and piperine moderately reversed the altered biochemical variables. On the other hand the combination of these was found to completely reverse the beryllium-induced biochemical alterations and oxidative stress consequences [122] .…”
Section: Recent Advances Of Bioenhancersmentioning
confidence: 99%
“…They observed that individual administration of gallic acid and piperine moderately reversed the altered biochemical variables. On the other hand the combination of these was found to completely reverse the beryllium-induced biochemical alterations and oxidative stress consequences [122] .…”
Section: Recent Advances Of Bioenhancersmentioning
confidence: 99%
“…Other researches documented the chemopreventive efficacy of Piperine is probably due to their antilipidperoxidative and antioxidant potential as well as its modulating effect on the carcinogen detoxification process [28,29] . Piperine is also known to enhance the bioavailability of some drugs by inhibiting drug metabolism or by increasing absorption [12,30,31] . Piperine with other antitumor drugs such as 5-FU [12] , piplartine [13] augmented the antitumor activity and also decreased the side effects.…”
Section: Wwwchinapharcom Lai Lh Et Almentioning
confidence: 99%
“…Piperine can reverse the corticosterone induced reduction of brain-derived neurotrophic factor mRNA expression in cultured hippocampal neurons [44]. Gallic acid exerts a synergistic effect when administered with piperine and provides a more pronounced therapeutic potential in reducing beryllium-induced hepatorenal dysfunction and oxidative stress consequences [63]. Piperine contains pentacyclic oxindole group which is effective for immunomodulation.…”
Section: Herbal Bioenhancersmentioning
confidence: 99%